1995
DOI: 10.1007/bf01874762
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of the Sardinian isolate of tomato yellow leaf curl geminivirus with its whitefly vectorBemisia tabaci Gen

Abstract: Relationships of an Italian isolate of tomato yellow leaf curl geminivirus from Sardinia (TYLCV-S) with its whitefly vector Bemisia tabaci were studied by means of experimental transmissions from tomato to tomato plants. TYLCV-S was confirmed to be transmitted in a persistent, circulative manner. The minimum latent period in the vector was between 17 and 20 h from the beginning of the acquisition access period (AAP). The maximum retention of infectivity was 8 days from the end of the AAP. Both acquisition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 13 publications
2
27
0
4
Order By: Relevance
“…6A). In the control, transmission efficiency of the wt virus fell within the expected values for a 12-h AAP (17). No inhibition was observed with the PNHD mutant.…”
Section: Vol 83 2009 Relationships Of Tylcsv Mutants With the Insecmentioning
confidence: 56%
See 2 more Smart Citations
“…6A). In the control, transmission efficiency of the wt virus fell within the expected values for a 12-h AAP (17). No inhibition was observed with the PNHD mutant.…”
Section: Vol 83 2009 Relationships Of Tylcsv Mutants With the Insecmentioning
confidence: 56%
“…The main parameters governing acquisition and transmission of TYLCSV and the related species TYLCV are already known (17,19,20). The kinetic experiments reported here showed that the infectious and virion-forming NT mutants PNHD and PNHE, or at least their DNA, persisted in whiteflies as the wt virus did, indicating that they circulated in B. tabaci hemocoel and reached the head/prothorax organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While acquisition and transmission of TYLCV by B. tabaci have been studied in some detail (6,7,30,36), the molecular interactions between this geminivirus (as well as others) and its insect vector are still poorly understood. Similar to other whiteflyborne geminiviruses, B. tabaci transmits TYLCV in a persistent-circulative nonpropagative manner (15), while some evidence points to viral transcriptional activity in the vector (38).…”
mentioning
confidence: 99%
“…Whether this is because the different biotypes feed more voraciously on one plant than on another or whether they feed in different locations on or within the leaf (affecting virion acquisition), will require a further investigation. A difference in the transmission efficiency of TYLCV by B. tabaci biotypes has also been reported by Caciagli et al (1995) and McGrath and Harrison (1995). The reproductive activity of B and Q-biotypes of B. tabaci was shown to differ , and studies using the electrical penetration graph technique (EPG) on stylet penetration in relation to probing and feeding behaviour (Jiang et al, 2001) of these two B. tabaci biotypes also showed differences.…”
Section: Resumen Nota Corta Efecto Del Biotipo De Bemisia Tabaci En mentioning
confidence: 83%